Vending machines: Food safety and quality assessment focused on food handlers and the variables involved in the industry - Raposo, António (2015)
"The purpose of this paper was to analyse the quality and safety parameters of food products sold in vending machines. A hygienic-sanitary assessment was conducted on 338 vending machines located on the island of Gran Canaria. Hygiene Assessment System (HAS) surveys, food handler examinations and microbiological (processed food and water) and physicochemical (water) controls were applied, permitting evaluation through the identification of the main risks and/or hazards of the hygienic-sanitary quality of the products sold in vending machines. Despite the positive results obtained from the HAS surveys applied to all the vending machines, achieving a total mean score of 87.6 ± 7.5 out of 100, the microbiological analysis showed that 5.7% of the 105 food samples were contaminated with Listeria monocytogenes, while Salmonella spp., Escherichia coli and Staphylococcus aureus were below the legally permitted limits. The lack of vehicles able to transport perishable food at correct temperatures (<8 °C) and the fact that some refrigerated vending machines were not at an ideal cooling temperature may have contributed to these values. The assessment tools used in this study revealed hygienic deficiencies in the transportation and microbiological quality of the products, despite the favourable results obtained in the HAS surveys and food handler examinations, indicating that this relationship should be the subject of further study to improve its usefulness in the field of Hazard Analysis and Critical Control Points."